Blocking Cross-Species Secondary Binding When Performing Double Immunostaining With Mouse and Rat Primary Antibodies - Mao, Shanping; Xiong, Guoxiang; Johnson, Brian N.; Cohen, Noam A.; Cohen, Akiva S. (Frontiers in Neuroscience, 2021)
Immunostaining is a powerful technique and widely used to identify molecules in tissues and cells, although critical steps are necessary to block cross-reaction. Here we focused at an overlooked cross immunoreactivity issue where a secondary antibody (secondary) cross-reacts with a primary antibody (primary) from a different species. We first confirmed the previously reported cross-species binding of goat anti-mouse secondary to rat primary. This was accomplished by staining with a rat primary against glial fibrillary acidic protein (GFAP) and visualizing with goat (or donkey) anti-mouse secondary. We then further revealed the converse cross-species binding by staining with a mouse primary against neuronal nuclear protein (NeuN) and visualizing with anti-rat secondaries. We speculate that mouse and rat primaries share antigenicity, enabling either secondary to recognize either primary. To block this cross-species binding in double staining experiments, we compared 3 protocols using mouse anti-NeuN and rat anti-GFAP, two primaries whose antigens have non-overlapping distributions in brain tissues. Simultaneous staining resulted in cross-species astrocytic staining (anti-mouse secondary to rat anti-GFAP primary) but no cross-species neuronal staining (anti-rat secondary to mouse anti-NeuN primary). Cross-species astrocytic staining was missing after sequential same-species staining with mouse anti-NeuN primary, followed by rat anti-GFAP. However, cross-species astrocytic staining could not be diminished after sequential same-species staining with rat anti-GFAP primary, followed by mouse anti-NeuN. We thus hypothesize that a competition exists between anti-mouse and anti-rat secondaries in their binding to both primaries. Single staining for NeuN or GFAP visualized with dual secondaries at different dilution ratio supported this hypothesis.